2020
DOI: 10.13189/ujer.2020.081318
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Learn Science as a Mediator between Attitude towards STEM and the Development of STEM Career Aspiration among Secondary School Students

Abstract: Education system plays an important role when it is able to produce skilled labour in the Science, Technology, Engineering and Mathematics field (STEM) for industrial need. Increasing students' interest to explore science by integrating STEM in the learning process is the main agenda for the global education system to ensure the learning outcome for students to excel in the future is achieved. Therefore, the need to cultivate the attitude towards STEM and the motivation to learn science is the drive in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The results from the testing are also supported by Murcia et al [36] who stressed the importance of parental influence inclusively in the academic progress of learners as it can affect the learners' career aspirations positively and is relevant towards the value of a career in the STEM industry. Parents can also have a positive impact and significantly encourage the mastery of science and math subjects by science stream students at the secondary level to ensure that their STEM career interests are well nurtured [26], [37]. Additionally, the findings are also supported by Vanmeter-Adams et al [38] stated that 65.5% of direct parental influence towards learners' academic progress and parents is the main significant component to increase learners' interest in STEM careers over the long-term.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results from the testing are also supported by Murcia et al [36] who stressed the importance of parental influence inclusively in the academic progress of learners as it can affect the learners' career aspirations positively and is relevant towards the value of a career in the STEM industry. Parents can also have a positive impact and significantly encourage the mastery of science and math subjects by science stream students at the secondary level to ensure that their STEM career interests are well nurtured [26], [37]. Additionally, the findings are also supported by Vanmeter-Adams et al [38] stated that 65.5% of direct parental influence towards learners' academic progress and parents is the main significant component to increase learners' interest in STEM careers over the long-term.…”
Section: Discussionmentioning
confidence: 86%
“…The demand for STEM has become the main issue in the global education system as there is a drastic increase in the demand for skilled labor in the STEM field. The importance of STEM awareness begins when the demands and the anticipated requirement of skilled workforce in the industry are not aligned with the students' participation enrolment at the secondary school level [25], [26]. Subsequently, this directly affects the graduates' participation in choosing STEM study fields at the HEI level [14], [27].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis conducted showed that science motivation has a significant direct influence in explaining the importance of science motivation towards the formation of STEM-related careers among students. Besides, motivation in learning science directly influences the environmental adaptability of students' learning process in choosing study programs related to STEM careers (Fazilah et al, 2020). The results have also shown that the combination of elements such as self-efficacy, self-determination, intrinsic motivation, grades, and career are needed to measure science motivation more thoroughly to inform students' interest towards STEM-related careers.…”
Section: Discussionmentioning
confidence: 99%
“…Bermudez used drone games in his study to teach students about navigation that are used in the aviation field. Students were introduced from the very early stages to the navigation system, and this can encourage students' motivation in space-related professions (Razali et al, 2020).…”
Section: Activities For Developing Ct In Stem Educationmentioning
confidence: 99%